Serum retinol concentration and prevalence of vitamin A deficiency in postpartum women - Juliana Cristina de Oliveira Dantas; Ana Caroline Perez Medeiros; Karla Danielly da Silva Ribeiro Rodrigues; Roberto Dimenstein (Universidade de Fortaleza, 2011)
Objective: To check the serum retinol concentration and assess the nutritional status of postpartum women assisted at Januario Cicco Maternity School, Natal / RN in relation to vitamin A deficiency. Methods: We recruited 190 healthy postpartum women assisted at aBrazilian public hospital. Serum retinol concentration was analyzed by high performance liquid chromatography. Retinol values below 30 μg g / dL were considered indicative of vitamin A deficiency. Results: The nutritional biochemistry status of vitamin A, regardingto serum retinol, presented an average of 44.6 ± 17.6 μg g / dL, showing normal values according to the referential (≤ 30 μg g / dL). However, 45 (23.7%) mothers had deficient levels of serum retinol, a prevalence which classifies the study population as a serious publichealth problem. Conclusion: The prevalence found in this study reports that the population is at risk for vitamin A deficiency, a situation clouded by the apparent normality of the mean serum retinol.